A new activator strontium for magnesium tetraborate: PL and TL studies. (October 2016) - Evis, D.; Yucel, A.; Kizilkaya, N.; Depci, T.; Kafadar, V.E.; Öztürk, E.; Yildirim, R.G.
Abstract: Strontium was used for the first time as an activator agent for magnesium tetraborate (MBO) and photoluminescence (PL) and thermoluminescence (TL) properties were determined using a spectrophotometer and a TL reader, respectively. The results proved that 0.25 wt% Sr ratio played an important role in prolonging the afterglow and the phosphor gave the main TL peak with the highest intensity at 200 °C like an ideal case. Therefore, it is worthwhile to carry out continuous and systematic research on it Highlights: It was the first time, strontium was used as an activator agent for magnesium tetraborate (MBO). Photoluminescence (PL) and thermoluminesance (TL) properties of Sr-doped MBO were investigated. Sr ions are related with the luminescence centers not with the electron traps for MBO. Sr is a promising activator for MBO and worth to continuous researches on it.